2005
DOI: 10.1074/jbc.m509557200
|View full text |Cite
|
Sign up to set email alerts
|

Altered Glycosylated PrP Proteins Can Have Different Neuronal Trafficking in Brain but Do Not Acquire Scrapie-like Properties

Abstract: N-Linked glycans have been shown to have an important role in the cell biology of a variety of cell surface glycoproteins, including PrP protein. It has been suggested that glycosylation of PrP can influence the susceptibility to transmissible spongiform encephalopathy and determine the characteristics of the many different strains observed in this particular type of disease. To understand the role of carbohydrates in influencing the PrP maturation, stability, and cell biology, we have produced and analyzed ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 58 publications
3
48
0
Order By: Relevance
“…24 Furthermore, the glycosylation patterns of PrP C may also affect protein trafficking and biophysical features. 25 It demonstrates an accumulation of PrP C in the Golgi compartment of neurons from transgenic mice expressing only nonglycosylated PrP C , although neither neurological signs nor neurodegeneration were found in these mice.…”
Section: The Role Of Cellular Prion Protein In Cell Activationmentioning
confidence: 99%
“…24 Furthermore, the glycosylation patterns of PrP C may also affect protein trafficking and biophysical features. 25 It demonstrates an accumulation of PrP C in the Golgi compartment of neurons from transgenic mice expressing only nonglycosylated PrP C , although neither neurological signs nor neurodegeneration were found in these mice.…”
Section: The Role Of Cellular Prion Protein In Cell Activationmentioning
confidence: 99%
“…To the authors' knowledge, there are no other species with a PrP polymorphism causing the loss of the first glycosylation site, so it would be interesting to investigate its functional consequences. Transgenic mice carrying the PrP substitution threonine for asparagine 181, which eliminates the first glycosylation site, show that the lack of glycans does not influence PrP maturation and stability and that the presence of one sugar chain is sufficient for trafficking to the cell membrane (Cancellotti et al, 2005). In the other cetacean species examined in this study, the N-linked glycosylation sites were found to be conserved.…”
Section: C-terminal Regionmentioning
confidence: 73%
“…In vitro studies suggest that glycosylation of PrP C affects its interaction with PrP Sc (Priola & Lawson, 2001), but that glycosylation is not required for strain properties (Nishina et al, 2006, Piro et al, 2009. Initial reports from studies in cell lines suggested that removing prion glycosylation produced spontaneously misfolded protein (Lehmann & Harris, 1997), however, this may have been a result of overexpression, since more recent studies have shown that blocking glycosylation of endogenously expressed PrP C does not produce this phenotype (Cancellotti, et al, 2005). In some cases, studies have been hampered by the folding and trafficking abnormalities that can occur when PrP C is expressed without glycosylation (Cancellotti, et al, 2005 depending on the specific mutations used to prevent glycosylation (Capellari et al, 2000, Ikeda et al, 2008, Salamat et al, 2011, Wong et al, 2000b.…”
Section: Factors Contributing To Prion Protein Misfoldingmentioning
confidence: 92%
“…This localises all relevant molecular species in the compartment in which the first morphological changes are detected, but this is still someway short of proving that abnormal PrP is neurotoxic. Through ongoing studies in our laboratories, we are endeavouring to dissect the relationship between PrP Sc , infectivity, neurotoxicity and mechanisms of neurodegeneration , Bradford et al, 2009, Cancellotti et al, 2010, Cancellotti et al, 2005, Manson et al, 2001, Piccardo, et al, 2007, Tuzi et al, 2008, Tuzi et al, 2004. Through the use of several unique models of prion disease in mice, we are beginning to accumulate evidence suggesting that the levels of infectivity are not always dependent on the quantity of misfolded PrP present , Piccardo, et al, 2007.…”
Section: Neurotoxicity Of Different Aberrantly Folded Prp Isoformsmentioning
confidence: 99%